Analysis of the Influence of Audit Service Quality on Auditee Satisfaction in the Internal Audit Division - Zulhendrianto; Khairani Ratnasari Siregar (Journal of International Multidisciplinary Research, 2025)
The increasing complexity and dynamics of the business environment at local, regional, and global levels have driven PT PLN (Persero)’s Internal Audit Unit (SPI) to adopt a Purpose-Driven Internal Audit approach, positioning the audit function as a strategic partner for long-term organizational success. However, the Internal Stakeholder Satisfaction Index for assurance services in the Construction, Generation, and New Renewable Energy Audit Division (AKP) fell short of its targets in 2023 and 2024. This study aims to analyze the impact of audit service quality—comprising tangibles, reliability, responsiveness, assurance, and empathy—on auditee satisfaction. Using a quantitative approach with PLS-SEM and Importance–Performance Map Analysis (IPMA), data were collected from AKP Division auditees in 2024. The results show that all dimensions of audit service quality positively and significantly influence satisfaction, with responsiveness and empathy being the most dominant factors. The findings offer practical insights for SPI PLN in prioritizing service improvements based on user perceptions and provide theoretical support for the SERVQUAL model as a key psychological mechanism in fostering satisfaction within trust-based professional services